Iodine deficiency as an environmental risk factor for thyroid gland diseases in animals - І. P. Ligomina; I. M. Sokulskyi; V. M. Sokolyuk; B. V. Gutyj; L. M. Soloviova (Ukrainian Journal of Veterinary and Agricultural Sciences)
Among non-infectious diseases in humans and animals, iodine deficiency pathology is a significant problem worldwide due to its high prevalence and broad spectrum of clinical signs and consequences. Increasing anthropogenic pressure on the natural environment has led to an ecological crisis. The situation is complicated in the biogeochemical zones of Ukraine, where insufficient or excessive content of mobile forms of microelements in soils and water sources determines the biological reaction of local flora and fauna. In animals, this is manifested by endemic diseases, including hypothyroidism. Mineral elements, including iodine, are a structural material in the body of animals; they participate in the processes of digestion and absorption in the digestive tract, synthesis, splitting, and excretion of metabolic products, creating the necessary conditions for the normal functioning of enzymes, hormones, vitamins, stabilize acidic-alkaline balance and osmotic pressure. Of all the organs of the endocrine system, the thyroid gland is the most closely related to the environment since its structure and function largely depend on the supply of iodine from the outside. The authors describe in detail the role of synergists of iodine (selenium, iron, copper, zinc, cobalt) and antagonists, the imbalance of trace elements, the influence of ionizing radiation, and the nature of feeding. It is substantiated that the action of environmental elements and anthropogenic factors determines the appearance and risk of developing thyroid pathology in cows. The article presents materials from a complex study of the clinical course of iodine deficiency, as well as morphological and biochemical parameters of the blood of cows. The object of research is clinically healthy and sick animals – cattle. Diagnosis of thyroid pathology was carried out with the help of clinical and laboratory tests. The clinical examination of cows was carried out according to the generally accepted scheme, taking into account the results of the general condition and studies of individual organs and systems. The research was conducted in three districts of the Zhytomyr region (Korostenskyi, Narodytskyi, and Popilnianskyi). During the external examination of the animals, swelling in the intermaxillary space (Myxedema) was observed, which was found only in 5 out of 90 dairy cows (5.6 %), mainly from Narodytsky district (8.9 %), compared to 2.2 % in Korosten district. It was observed that goiter was established in only three cows out of 90 (3.35%); all were in Narodytsky district (6.7 %). Enophthalmos was detected in 24 out of 90 dairy cows (26.7 %), including 16 out of 45 cows (35.4 %) in the Narodytsky District, while this symptom was not detected in the Popilnya District dairy cows. It was established that the content of thyroxine in dairy cows of Narodytskyi and Korostensky districts ranged from 2.2 to 4.25 μg/100 ml (28.3–54.7 nmol/l), respectively, and was on average 3.4 ± 0.21 μg/100 ml (43.8 ± 2.70 nmol/l, in cows from the conditionally clean territory (Popelnyan district) – 5.3 ± 0.65 nmol/l.